Managing Innovation in Diverse Settings: STEM Education Implementation and Student Motivation Across Socioeconomic Contexts - Dini Indriani; Iim Wasliman (Papanda Publisher, 2026)
STEM education implementation in resource-constrained contexts faces persistent challenges despite its recognized importance for developing 21st-century competencies. While pedagogical approaches have been extensively studied, the critical role of educational management in mediating implementation effectiveness remains undertheorized. This qualitative comparative case study examined STEM learning management practices in two Indonesian junior high schools serving contrasting socioeconomic populations. Data were collected through semi-structured interviews with 12 participants (principals, teachers, students), systematic classroom observations, and document analysis. Analysis followed Miles and Huberman's interactive model, employing multiple triangulation strategies. Findings revealed that systematic management practices—particularly comprehensive planning, dedicated organizational structures, and responsive supervision—enabled more sophisticated STEM implementation characterized by greater student autonomy and deeper investigative processes. Resource-abundant SMPN 4 demonstrated quarterly planning cycles and formalized coordination, while resource-limited SMPN 5 employed semi-annual cycles with integrated coordination. Unexpectedly, both schools achieved high student motivation through differentiated pathways: career-oriented at SMPN 4 versus social-practical at SMPN 5. Systematic learning management constitutes a critical enabler for effective STEM implementation, with quality management practices partially compensating for material resource limitations. Findings challenge deficit perspectives by demonstrating that culturally responsive, well-managed STEM programs can foster engagement across diverse socioeconomic contexts.